Russian Orthodoxy Resurgent - Garrard, Josh and Carol (Princeton Princeton University Press, 2008)
In this rewarding book, the Garrads humanize and deliver with great learning the epic story of the revival of the Russian Orthodox Church. They illuminate a lost experience by studying the church through the prism of its spectacular civic rebirth.
Keywords: History